Assessment of Thailand’s Health System Performance in 2022-2023 - Pokpermdee, Pongsadhorn; Sukpatthanakul, Krittiya; Phimla, Soradakorn; Pensuriya, Wanwisa; Charoensuntisuk, Nardanong; Kongsueb, Punnipa; Chantra, Sasipa; Khingchatturat, Natnaree; Kanta, Isariyaporn; Nuthong-In, Onjira; Karnchanayothin, Nichatorn; Akaleephan, Chutima (Journal of Health Systems Research, 2024)
Background: The assessment of Thailand’s health system performance from 2022 to 2023 aims to analyze health outcomes in comparison to the OECD (Organisation for Economic Co-operation and Development) and ASEAN (Association of Southeast Asian Nations) countries. The study aimed to examine and synthesize the relationships between health expenditures and key indicators, and to prioritize the health indicators that Thailand urgently needed to achieve from among the 193 OECD health indicators. The goal was to formulate policy and strategic recommendations that enhance the sustainability and international competitiveness of Thailand’s health system. Methodology: This study used a mixed methods approach to analyze both the quantitative and qualitative aspects of health system outcomes. It explored the relationship between health expenditures and key indicators by comparing Thailand’s data with that of OECD and ASEAN countries. The study also incorporated a two-round modified Delphi survey, gathering anonymous expert opinions online to frame top priority indicator groups with final policy recommendations. Results: Thailand data covered 158 indicators and lacked 35 indicators. Of those available, 112 indicators were comparable with the OECD countries, while 46 non-comparable indicators were those with trends, proportions, or qualitative data. Main findings were: 1) out of 5 dimensions of the comparable indicators, there were 51 indicators that Thailand health system outperformed the OECD average and 61 indicators that lagged behind the OECD average. (1) Within the health status dimension, 17 indicators were identified as challenges, with 8 indicators requiring immediate attention. The top three indicators in need of urgent development were the maternal mortality ratio, infant mortality rate, and the prevalence of type 1 and type 2 diabetes in adults. (2) Under the health risk factor dimension, 12 indicators were challenges while top three were the premature birth rate, the smoking rate among children aged 13-15 by gender, and the smoking rate among the population aged 15 and over by gender. (3) Under the service access dimension, 12 indicators were challenges and top three were the ratio of doctors per 1,000 population by region, the proportion of household expenditure on health, and the proportion of patients waiting for cataract surgery over three months. (4) Under the patient care quality dimension, 11 indicators were challenges, with 16 indicators in need of urgent development, while top three were the percentage of the population aged 65 received influenza vaccine, the proportion of antimicrobial resistance in long-term care, and the suicide rate among inpatients with psychiatric illnesses. (5) Under the health resource dimension, 9 indicators were challenges, 18 required urgent attention, and top three priorities were the number of critical care beds, the number of nursing graduates, and the number of nurses per 1,000 population. 2) From the prioritization of the 61 indicators needed urgent development, the top five indicators deemed most critical by experts were: the number of critical care beds, the production of nursing graduates, and three indicators tied for the third place were the maternal mortality ratio, the rate of foreign body left after procedure, and the number of nurses per 1,000 population. The fourth priority was the percentage of the population aged 65 and over received influenza vaccine. The fifth priority included the proportion of antimicrobial resistance in long-term care; government expenditure on health as a percentage of total government expenditure; and the number of physicians per 1,000 population. 3) The correlation study between health expenditure and health outcomes showed that Thailand and other ASEAN countries with low per capita health spending–mostly developing nations–had poorer health outcomes compared to more developed OECD countries. Despite relatively low health expenditure, these countries often achieve good accessibility, quality of care, and coverage of essential health services. Thailand’s per capita health expenditure was 25,472 baht (730.5 USD PPP), lower than the OECD average. Nevertheless, Thai population benefited from universal access to core health services. 4) The results of policy and strategic proposals for driving and developing the capacity of Thailand health system sustainably were divided into proposals for managing the development of 5 dimensions of health system outcomes: focusing on creating health literacy; developing health care system for older persons; developing the service system, especially the primary care system, reorienting medical services to the community; by planning the management and distribution of resources comprehensively; and creating a development plan to achieve health outcomes according to the OECD targets in terms of management of critical patient beds and nurse production. Conclusion: Thailand’s health system performance showed improvement and ranked high in ASEAN, however, the health outcomes fell short when compared to developed countries. Therefore, it is essential for Thailand to further enhance the efficiency of its health system to achieve better quality health outcomes for its population.